The sum of two complementary angles is 90 degrees.
Therefore, the equation can be written as:
(x + 2) + (2x - 4) = 90.
A figure displays two nonadjacent angles with measures (x + 2) and (2x - 4) . If the two angles are complementary, what is the written equation?
(x + 2) + ( ) = __
11 answers
The complementary angles have measures (4x) and (2x) . What is the value of x and the two angle measures?
x = __ (4x) = __ , and (2x) = __
x = __ (4x) = __ , and (2x) = __
The sum of two complementary angles is 90 degrees.
Therefore, (4x) + (2x) = 90.
Combining like terms, we get 6x = 90.
Dividing both sides by 6, we find that x = 15.
Substituting this value back into the expressions for the angle measures:
(4x) = 4(15) = 60
(2x) = 2(15) = 30
So, the values are:
x = 15
(4x) = 60
(2x) = 30
Therefore, (4x) + (2x) = 90.
Combining like terms, we get 6x = 90.
Dividing both sides by 6, we find that x = 15.
Substituting this value back into the expressions for the angle measures:
(4x) = 4(15) = 60
(2x) = 2(15) = 30
So, the values are:
x = 15
(4x) = 60
(2x) = 30
In a figure, one complementary angle has a measure of 36 and the other has a measure of (x - 3) . What is the value of x and the value of x and the value of the unknown angle measure?
X = __ , unknow angle measure = __
X = __ , unknow angle measure = __
The sum of two complementary angles is 90 degrees.
Therefore, we can set up the equation:
36 + (x - 3) = 90.
Combining like terms, we get x + 33 = 90.
Subtracting 33 from both sides, we find that x = 57.
Substituting this value back into the expression for the unknown angle measure:
(x - 3) = (57 - 3) = 54.
So, the values are:
x = 57
Unknown angle measure = 54.
Therefore, we can set up the equation:
36 + (x - 3) = 90.
Combining like terms, we get x + 33 = 90.
Subtracting 33 from both sides, we find that x = 57.
Substituting this value back into the expression for the unknown angle measure:
(x - 3) = (57 - 3) = 54.
So, the values are:
x = 57
Unknown angle measure = 54.
A figure displays two nonadjacent angles with measures 3x and (4x + 1) . If the angles are complementary, what is the simplified equation corresponding to the measures of the angles?
answers:
(7x + 1) = 90
(7x + 1) = 180
(1x + 1) = 90
(1x + 1) = 180
answers:
(7x + 1) = 90
(7x + 1) = 180
(1x + 1) = 90
(1x + 1) = 180
The sum of two complementary angles is 90 degrees.
Therefore, the equation corresponding to the measures of the angles is:
3x + (4x + 1) = 90.
Combining like terms, we get:
7x + 1 = 90.
So, the simplified equation is:
(7x + 1) = 90.
Therefore, the equation corresponding to the measures of the angles is:
3x + (4x + 1) = 90.
Combining like terms, we get:
7x + 1 = 90.
So, the simplified equation is:
(7x + 1) = 90.
What are the two angle measures of complementary angles expressed as 3x and (2x - 5) ?
answers:
19 and 71
21 and 69
30 and 60
33 and 57
answers:
19 and 71
21 and 69
30 and 60
33 and 57
The sum of two complementary angles is 90 degrees.
Therefore, we can set up the equation:
3x + (2x - 5) = 90.
Combining like terms, we get 5x - 5 = 90.
Adding 5 to both sides, we find that 5x = 95.
Dividing both sides by 5, we find that x = 19.
Substituting this value back into the expressions for the angle measures:
3x = 3(19) = 57
2x - 5 = 2(19) - 5 = 38 - 5 = 33
So, the two angle measures are 57 and 33.
Therefore, we can set up the equation:
3x + (2x - 5) = 90.
Combining like terms, we get 5x - 5 = 90.
Adding 5 to both sides, we find that 5x = 95.
Dividing both sides by 5, we find that x = 19.
Substituting this value back into the expressions for the angle measures:
3x = 3(19) = 57
2x - 5 = 2(19) - 5 = 38 - 5 = 33
So, the two angle measures are 57 and 33.
Two angles are complementary. One angle has a measure of 40 and the other has a measure of (8x + 2) . What is the value of x?
answers:
50
11
60
6
answers:
50
11
60
6
The sum of two complementary angles is 90 degrees.
Therefore, we can set up the equation:
40 + (8x + 2) = 90.
Combining like terms, we get 8x + 42 = 90.
Subtracting 42 from both sides, we find that 8x = 48.
Dividing both sides by 8, we find that x = 6.
So, the value of x is 6.
Therefore, we can set up the equation:
40 + (8x + 2) = 90.
Combining like terms, we get 8x + 42 = 90.
Subtracting 42 from both sides, we find that 8x = 48.
Dividing both sides by 8, we find that x = 6.
So, the value of x is 6.